2016
DOI: 10.1038/srep30682
|View full text |Cite
|
Sign up to set email alerts
|

A quantitative assessment of Arctic shipping in 2010–2014

Abstract: Rapid loss of sea ice is opening up the Arctic Ocean to shipping, a practice that is forecasted to increase rapidly by 2050 when many models predict that the Arctic Ocean will largely be free of ice toward the end of summer. These forecasts carry considerable uncertainty because Arctic shipping was previously considered too sparse to allow for adequate validation. Here, we provide quantitative evidence that the extent of Arctic shipping in the period 2011–2014 is already significant and that it is concentrated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
98
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 161 publications
(111 citation statements)
references
References 15 publications
(21 reference statements)
2
98
0
1
Order By: Relevance
“…Mean shipping activity (kilometers traveled) in the Canadian Arctic from 1990 to 2015 occurred primarily in regions of north Hudson Bay, the Hudson Strait, Davis Strait, Baffin Bay, Lancaster Sound, and the south Beaufort Sea (Figure a). The spatial distribution is similar to the pattern illustrated by Eguíluz et al [] based on AIS data from 2010 to 2014. Regions of high shipping activity typically correspond to areas of lighter sea ice concentration, as the majority of high sea ice concentration is located in central CAA and the north regions of Beaufort Sea (Figure c).…”
Section: Spatial Distribution Of Shipping Activity and Sea Ice Concensupporting
confidence: 86%
See 1 more Smart Citation
“…Mean shipping activity (kilometers traveled) in the Canadian Arctic from 1990 to 2015 occurred primarily in regions of north Hudson Bay, the Hudson Strait, Davis Strait, Baffin Bay, Lancaster Sound, and the south Beaufort Sea (Figure a). The spatial distribution is similar to the pattern illustrated by Eguíluz et al [] based on AIS data from 2010 to 2014. Regions of high shipping activity typically correspond to areas of lighter sea ice concentration, as the majority of high sea ice concentration is located in central CAA and the north regions of Beaufort Sea (Figure c).…”
Section: Spatial Distribution Of Shipping Activity and Sea Ice Concensupporting
confidence: 86%
“…However, the detrended correlation between the two variables is low [ Pizzolato et al , ]. Despite speculation that declining sea ice may be, to some extent, influencing shipping trends in the region, several other studies have suggested that tourism trends, commodity prices, and natural resource development are likely much more influential than declining sea ice [e.g., Bensassi et al , ; Brigham , ; Dawson et al , ; Eguíluz et al , ]. Even with these varying perspectives, the spatial variability of sea ice and its corresponding influence on shipping in Canadian Arctic waters has not been quantified over multidecadal time periods.…”
Section: Introductionmentioning
confidence: 99%
“…The reduction in extent of Arctic sea ice [e.g., Perovich et al ., ; Meier et al ., ] combined with a reduced thickness [e.g., Giles et al ., ; Kwok and Cunningham , ] and a reduction in the amount of multiyear or perennial ice [e.g., Comiso , ] means that the Arctic is becoming more accessible for shipping, maritime activities, and the tourist industry [ Brigham , ; Eguíluz et al ., ]. While the two former strive to avoid the sea ice as much as possible and will, if ice is encountered, aim for a route through thinner ice to save time and fuel; the latter often try to get close to the sea ice for better visual contact.…”
Section: Introductionmentioning
confidence: 96%
“…Climate change is opening new waterways in the Arctic Ocean, resulting in greater shipping traffic (ACIA 2004;Arctic Council 2009;Guy & Lasserre, 2016). Predicted increases in shipping frequency and routes (Eguíluz, Fernández-Gracia, Irigoien, & Duarte, 2016;Miller & Ruiz, 2014;Smith & Stephenson, 2013), increased infrastructure development in ports (Gavrilchuk & Lesage, 2014), and associated chemical/biological pollution will place other ecosystem services at risk. Furthermore, the introduction of nonindigenous species (NIS) may displace native species, alter habitat and community structure and increase aquaculture and fishing gear fouling in estuaries and coastal zones (Goldsmit et al, 2018;Grosholz, 2002;Parker et al, 1999).…”
Section: Introductionmentioning
confidence: 99%